Incongruencias entre el art. 131 de la ley orgánica de transporte terrestre, tránsito y seguridad vial, y, el núm. 6 del art. 76 de la constitución de la república, lo que implica la no aplicación del principio de proporcionalidad en dicha norma de transito - Tubón Tite, Luis Hernan (2014)
The hierarchical superior will solve the petition or birdcall in the term of 15 days, conquered which will understand each other, for the administrative silence that the application has been approved or that the reclamation was solved in the petitioner's" favor. The user of the public administration, is in the imperium of requesting to the public administration that you/they are made be worth his rights, when for his to work incumplan the laws of environmental protection, and that his to proceed violates the preceptuado. This order should be based on right, and, in the possible smallest time to receive its answer. In yes, it is an administrative procedure that a person exercises affected in her subjective rights or legitimate interests as consequence of actions or administrative omissions. In this norm, to execute the sanction of the omission of the environmental norms, he/she can make it by means of the administrative birdcall. The juridical principles that govern to the Administrative Birdcalls, define the essence and existence of the procedures "allowing to explain beyond the regulations dogmatic prodecimentales, their reason and its for what reason." The administrative Birdcall is applicable to any organ of the State, and, in our central topic of my thesis, to the atmosphere, the administrative birdcall proceeds in the face of authorities of institutions in charge of watching over the environment and that they are linked to the Ministry of Atmosphere